Correlating 0νββ decays and flavor observables in leptoquark models - S. Fajfer; L. P. S. Leal; O. Sumensari; R. Zukanovich Funchal (Journal of High Energy Physics)
Abstract In this paper, we investigate minimal scalar leptoquark models that dynamically generate neutrino Majorana masses at the one-loop level and examine their implications for low-energy processes. We show that these models can produce viable neutrino masses, consistent with neutrino oscillation and cosmological data. By using leptoquark couplings fixed by neutrino data, we predict additional contributions to neutrinoless double-beta decays (0νββ), which are chirality enhanced and compete with the standard contributions from the Majorana masses. Our analysis demonstrates that these effects are sizable for leptoquark masses as large as O 300 TeV $$ \mathcal{O}\left(300\ TeV\right) $$ , potentially increasing or decreasing the 0νββ half-life, and creating an ambiguity between the normal and inverted mass ordering scenarios. Furthermore, we explore the correlation between 0νββ and flavor observables, such as kaon decays and μ → e conversion in nuclei, emphasizing that the latter is complementary to 0νββ decays.